The Coloniality of Perception: The Other as a Cannibal - Kubiaczyk, Filip (Poznańskie Towarzystwo Przyjaciół Nauk, 2013)
The article addresses the problem of the coloniality of perception, or visual-semantic manipulation of racial context which accompanied the development of the modern/ colonial capitalism. In this regard, I demonstrate that the gure of cannibal as a cultural trope played a key role in the symbolic appropriation of the New World by the Europeans, which paved the way for its military, political and economic conquest. By drawing on the source accounts, I show how the cannibal trope changed its geographical and semantic range, arranging the colonial discourse on the Other.
Keywords: the Other; cannibalism; cannibal; Cannibalia; difference; anthropophagy; the New World; cartography; cultural trope